Portrait of Chhatrapati Shivaji Maharaj - Ghosh, Ayan (2023)
Post-independence, images of British administrators were removed, and new icons were added. Among the new installations was this portrait of Chhatrapati Shivaji Maharaj placed in the lobby of the grand staircase. Not only is Shivaji Maharaj a national hero, during his lifetime, but he was also much praised for taking an interest in the welfare of his people, in line with the core objective of the BMC—to uplift the quality of life of Mumbai's citizenry.